Conceptualizing the Ideal University-Level Learning Transformation in Indonesia: Industry-Higher Education Collaboration in a Technology-Based Learning Management System - Moh. Aziz Rohman; Irfan Faozun; Makmur Syam (Universitas Dharma Wacana, 2022)
This research aims to develop problem-solving strategies for strength-opportunity, weakness-opportunity, strength-threat, and weakness-threat analysis in the context of developing and implementing an Integrated Learning Management System (ILCMS) in universities. Based on the results of the SWOT analysis, some suggested strategies include building partnerships and collaboration between universities, integrating student skills, improving infrastructure, adopting the latest technology, and advocating to the government. These strategies are expected to strengthen the implementation of SMPT and improve the quality of education in universities. In addition, this research also explores problem-solving strategies against the strength-threat, weakness-opportunity, and weakness-threat analyses. These strategies include building industry partnerships and student empowerment. These partnerships create a collaborative environment between companies and universities, where companies provide students with insights, resources and job opportunities. In addition, universities can also collaborate with companies in designing curricula that are relevant to industry needs, so that students can get an education that is in line with the latest developments. Industry partnerships and student empowerment also provide benefits to companies, such as access to talent and influence on curriculum development and research. In order to achieve successful partnerships, it is important for universities and companies to engage in open dialog, listen to each other, and appreciate each other's perspectives. In addition, universities need to prepare students with the cross-disciplinary skills and adaptability required in the world of work. By implementing these strategies, universities can optimize the use of technology in education, improve infrastructure, address the digital divide, and enhance the quality of learning. In addition, industry partnerships and student empowerment are expected to create a relevant educational environment and prepare a competent workforce to face future challenges.